Characterization of individuals with osteoarthritis in the United States and their use of prescription and over-the-counter supplements. (March 2021) - Lane, Nancy E.; Ivanova, Jasmina; Emir, Birol; Mobasheri, Ali; Jensen, Morten Georg
Highlights: Osteoarthritis is the most common form of arthritis, affecting a high proportion of the elderly population in the US. Recent clinical studies have provided promising data supporting the use of natural products as supplements for treating osteoarthritis. This cross-sectional study based on consumer research data showed that individuals with osteoarthritis have a high body mass index and rates of comorbid diseases and do not exercise on a regular basis. Individuals with osteoarthritis using chondroitin with or without glucosamine were more likely to report use of over-the-counter products only or to use them combined with prescription products. The likelihood of using prescription products increased with the length of osteoarthritis history, highlighting new opportunities for nonsurgical management. Abstract: Purpose: Osteoarthritis (OA) is a frequently occurring, chronic condition; however, few studies describe the clinical characteristics of individuals with OA and the treatments they use to manage their symptoms. We conducted a study to characterize the OA population in the US and describe the nonsurgical management used by this population based on consumer research data collected through an online survey. Methods: Data from the 2017 US National Health and Wellness Survey (NHWS) for adults aged ≥35 years were used to evaluate the relationship between OA and certain study participant characteristics and to identify the most commonly used treatment options. NHWS data were collected through a survey of individuals drawn from the internet panel maintained by Lightspeed Research (Bridgewater, New Jersey) and its panel partners. Weighted estimates were generated using data from the 2016 Current Population Survey (Annual Demographics File) of the US Census Bureau. Comparisons between the general and OA populations were made based on body mass index (BMI), exercise frequency, and comorbid diagnoses of hypertension or diabetes. Among the OA population, the use of dietary supplements, prescription or over-the-counter (OTC) treatments with chondroitin with or without glucosamine (Ch ± Gl), prescription treatment by time since OA diagnosis, and utilization of a physical therapist were also recorded. Results: The prevalence of OA in the overall population was 17.6 % and was higher for individuals with a BMI ≥ 25 (21.9 %), patients diagnosed with hypertension or diabetes (36.2 %), and those who did not exercise regularly (19.0 %). Adults without OA were more likely to exercise regularly (12 days per month or more) than adults diagnosed with OA. Ch ± Gl (6.0 %) was the most commonly used OTC dietary supplement in the OA population, followed by omega-3 fatty acids (2.8 %), vitamin D (1.9 %), calcium (1.1 %), and multivitamins (0.7 %). Individuals using Ch ± Gl were more likely to use OTC only products (75.4 % vs 37.3 %) or prescription medications, namely non-steroidal anti-inflammatory drugs (NSAIDs) and/or opioids, and OTC products (24.6 % vs 13.0 %) compared with individuals not using Ch ± Gl, while individuals not using Ch ± Gl were more likely to be untreated (30.3 % vs 0) or to use prescription medications only (19.4 % vs 0). Nearly 32 % of individuals with OA reported using prescription treatments, and the likelihood of using a prescription treatment increased with number of years since OA diagnosis (<3 years: 27.5 %; ≥21 years: 32.5 %). The pharmaceutical products used by this population primarily consisted of nonsteroidal anti-inflammatory drugs, acetaminophen and opioids. Approximately 13 % of patients with OA had visited a physical therapist in the past 6 months. Conclusions: The prevalence of OA was higher in those with a high BMI, and comorbid diabetes or hypertension. Individuals with OA using Ch ± Gl primarily reported use of OTC products only or used them in combination with prescription products. The likelihood of using prescription products increased with the length of OA history. These data provide valuable new information about demographics, clinical characteristics, and commonly used prescription and OTC treatments and dietary supplements in the OA population.